The Effects of Structural Change on Economic Growth: A Panel Data Analysis - Trofimov, Ivan D. (Panoeconomicus, 2023)
This paper attempts to enhance empirical understanding of the effects of structural-change variables on economic outcomes. The relationships between sectoral shares and (1) the speed of structural change and (2) economic growth were examined for a large panel of 111 economies over the period of 1971–2018. Given the time series properties of the series and the absence of a long-run relationship between them, the panel OLS and VAR models were employed. The results are largely in line with previous empirical research: it was established that a lack of industrialisation effort (manifested in the persistence of agriculture as a share of GDP) and ‘servicisation’ (the expansion of the services share of GDP) negatively affect GDP growth rates. In contrast, a growth in industry and manufacturing shares positively influences economic growth, as does accelerated structural transformation (represented by the respective index of structural change). JEL: L16, C33, O14, O57.